FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SEDIAAN KRIM BODY SCRUB EKSTRAK BUNGA KECOMBRANG (Etlingera elatior) DENGAN MENGGUNAKAN DPPH (2,2 diphenyl-1-picrylhyrazyl) - purnamasari, santri; Agustin, Gina Septiani (PHRASE (Pharmaceutical Science) Journal, 2025)
Body Scrub Cream contains coarse grains that function as sanders, or obrasivers, which can remove dead cells from the epidermis. Torch ginger flowers have antioxidant activity produced in the form of secondary metabolites, namely the flavonoid group, the main components of flavonoids, namely quercetin and kaempferol, function as antioxidants. The purpose of this study was to make a body scrub and test antioxidant activity with the DPPH method (2,2-diphenyl-1-picrylhydrazyl) is a stable radical, which can be used to evaluate antioxidant performance, with experimental methods. The results of this study were that Torch ginger flower extract can be used as a body scrub cream preparation with extract concentrations of 3%, 5%, and 7%. The antioxidant activity of the body scrub preparation formula III with an IC50 value of 29.66 (Very strong), formula I with an IC50 value of 71.24 and formula II with an IC50 value of 52.30 has strong antioxidant activity, which has a very strong IC50, namely Formula III with an extract concentration of 7%.